From gatekeepers to gateway constructors: Credit rating agencies and the financialisation of housing associations. (September 2020) - Smyth, Stewart; Cole, Ian; Fields, Desiree
Abstract: This paper uses the twin metaphors of 'gatekeeper' and 'gateway constructor' as devices to explore the role of Credit Rating Agencies (CRAs) as intermediaries between global corporate finance and specific institutions – housing associations in England. The analysis utilises a financialisation framing, whereby the practices, logics and measurements of finance capital, increasingly permeate government, institutional and household behaviour and discourse. This paper examines how housing associations have increasingly resorted to corporate bond finance, partly in response to reductions in government funding, and in the process engaged with CRAs. Surprisingly little research has been undertaken on the role and function of CRAs, and their impact on the organisations they rate. The case of housing associations (HAs) is of particular interest, given their historical social mission to build and manage properties to meet housing need, rather than operate as commercial private landlords conversant with market-based rationales. A case study of the large London-based HAs draws on a narrative and financial analysis of annual reports, supplemented by semi-structured interviews with senior HA finance officers to explore how CRA methodologies have been internalised and have contributed to changes in strategic and operational activities. We conclude that CRAs act both as a gatekeeper to the financial markets but also as a gateway constructor for the financial markets to enter new arenas, such as the HA sector. This dual nature of CRAs is intended as our contribution to emerging debates about the nature, the practice and the impact of financialisation on public services.